2018
DOI: 10.1080/00913847.2018.1513756
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound examination and patellar tendinopathy scores in asymptomatic college jumpers

Abstract: In short, hypoechoic areas were detected by US examination among self-reported asymptomatic jumpers. There was an association between hypoechoic areas and VISA-P scores in the right knee, but not in left knee. VISA-P scores may be used as a screening tool for the presence of hypoechoic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…It has been suggested that the size of the hypoechoic tendon area may be linked to the amount of pain [11]. Our results support the notion that symptomatic patellar tendons have greater volume or size, as reflected by greater CSA, width and thickness; however, these morphological changes were not associated with clinical features.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been suggested that the size of the hypoechoic tendon area may be linked to the amount of pain [11]. Our results support the notion that symptomatic patellar tendons have greater volume or size, as reflected by greater CSA, width and thickness; however, these morphological changes were not associated with clinical features.…”
Section: Discussionsupporting
confidence: 84%
“…It has been found that structural changes observed on ultrasound imaging can be associated with an increased risk of developing symptoms [9]; nevertheless, tendon pain is not always associated with the presence of abnormal findings on imaging studies [10]. In fact, there is a limited relationship between tendon imaging pathology and presence of symptoms since structural tendon changes can exist in the absence of symptoms, and symptoms can be present without the presence of imaging changes [11]. However, ultrasound imaging continues to be used as a confirmatory tool for a diagnosis of patellar tendinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of patellar tendinopathy of player group was 15.79% (6 knees) but only one knee was reported to be symptomatic (IKDC score 49), which indicated that most patellar tendinopathy revealed by ultrasonography in this group is asymptomatic. Fazekas et al surveyed 31 collegiate athletes involved in jumping movement, 13 of them were male and 9 knees were tested positive of ultrasonographic findings of patellar tendinopathy, but the correlation of positive image findings with the scoring of Victorian Institute of Sport Assessment Questionnaire for Patellar Tendinopathy (VISA-P) was poor and insignificant [26]. Our investigation also showed similar result.…”
Section: Discussionsupporting
confidence: 79%
“…The patellar tendon was measured from its inferior border to its tibial tuberosity, and its total length was divided by two to determine its middle section. The epitendon and paratendon were not included in the measurement 32 .…”
Section: Secondary Outcome Measures Functional Disabilitymentioning
confidence: 99%